Architectural specification, exploration and simulation through rewriting-logic - Ayala Rincón, Mauricio; Hartenstein, Reiner W.; Maya Neto, Rinaldi; Jacobi, Ricardo P.; Llanos, Carlos Humberto (Revista Colombiana de Computación, 2002)
In recent years Arvind’s Group at MIT has shown the usefulness of term rewriting theory for the specification of processor architectures. In their approach processors specified by term rewriting systems are translated into a standard hardware description language for simulation purposes. Keywords: Rewriting-logic, High Level Specification and Simulation, Design Environment.